Looking for appropriate solutions to the economic crisis problem: the Cyprus bail-in example - Kountouris, Andreas (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
This essay was prepared to describe the reasons led to the economic crisis in Cyprus on March 2018. First of all the essay starts with the first Chapter which includes the facts that led to collapse of the Cyprus’ banking system before the disaster of March 2013. Following this stream of thoughts the second Chapter is dedicated to the sad facts of March 2013 and the consequences led to the bail-in. The third Chapter refers to the ‘next day’ of the crisis with the conditions and effects of this situation and it especially it analyses the trends that led to the Cyprus banking crisis and the consequences for the financial sector of Cyprus. In the last Chapter, Analysis, we prepared a multiple regression using the quarterly credit ratings for Cyprus from the three credit agents (S&P, Fitch and Moody’s) and quarterly values for six variables (Fiscal Balance, External Debt, GDP growth, Inflation, GDP per capital income, External Balance).
Keywords: Εconomic crisis; Cyprus; Βail-in